2022
DOI: 10.1088/1555-6611/ac6ac3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uneven temperature distribution on underwater computational ghost imaging

Abstract: The influence of uneven temperature distribution on imaging quality of computational ghost imaging (CGI) in the underwater environment is investigated experimentally. It is shown that as the water temperature increases, imaging quality presents a trend from deterioration to improvement. The results can be explained by the changes of the temperature difference between the upper and lower layers of underwater environment and laser spot travelling through the underwater environment. Moreover, the effect from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These patterns are used to form a reconstructed image through correlation calculation. Owing to its wide range of light sources and strong anti-interference ability, GI has attracted significant attention in several related fields such as X-ray imaging 1 , 2 , terahertz imaging 3 , acoustic imaging 4 , three-dimensional imaging 5 , 6 , fluorescence imaging 1 , optical encryption 7 , 8 , and underwater imaging 9 15 . The application scenarios and influencing factors of GI are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These patterns are used to form a reconstructed image through correlation calculation. Owing to its wide range of light sources and strong anti-interference ability, GI has attracted significant attention in several related fields such as X-ray imaging 1 , 2 , terahertz imaging 3 , acoustic imaging 4 , three-dimensional imaging 5 , 6 , fluorescence imaging 1 , optical encryption 7 , 8 , and underwater imaging 9 15 . The application scenarios and influencing factors of GI are depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There is a possibility to further reduce the sampling rate of GI using the properties of the orthogonal matrix. Due to the advantages and breakthroughs in key technologies, GI has been applied in some real environments, such as turbulent atmospheres [21], speckle media [22], underwater environments [23][24][25][26][27][28][29][30][31], super-resolved quantum [32], and microscopy field [33]. GI has the advantage of anti-disturbance, which provides a better option for underwater optical imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the imaging qualities of orthogonal and random speckle patterns in air 13 has shown that orthogonal speckle patterns are more suitable for low-sampling CGI. Owing to its wide range of light sources and strong antiinterference ability, GI has attracted significant attention in several related fields such as X-ray imaging 14,15 , terahertz imaging 16 , acoustic imaging 17 , three-dimensional imaging 18,19 , fluorescence imaging 14 , optical encryption 20,21 , and underwater imaging [22][23][24][25][26][27] . Application scenarios and influencing factors of GI are shown in Fig.…”
mentioning
confidence: 99%